Blamestorming, blamemongers and scapegoats : allocating blame in the criminal justice process - Dingwall, Gavin; Hillier, Tim (Policy Press, 2015)
We live in a society that is increasingly preoccupied with allocating blame: when something goes wrong someone must be to blame. Bringing together philosophical, psychological, and sociological accounts of blame, this is the first detailed socio-legal account of the role of blame in which the authors present a novel study of the legal process of blame attribution, set in the context of criminalisation as a social and political process. The book identifies the problematic and elusive nature of blame and contrasts this with the uncritical way in which it is often used in the criminal justice process.